Examining the Reach of Color Blindness: Ideological Flexibility, Frame Alignment, and Legitimacy among Racially Conservative and Extremist Organizations. Issue 2 (3rd April 2017) - Brooks, Erinn; Ebert, Kim; Flockhart, Tyler
ABSTRACT: To what extent do right-wing groups demonstrate internal alignment in their use of racial ideologies? Under what conditions with respect to internal alignment do mainstream media legitimize these groups by relaying their messages to the public as the organizations intended? We analyzed two decades' worth of organizational literature and media coverage to examine the relationship between internal and external frame alignment. The findings reveal that organizations display ideological flexibility in their public documents. Organizations receive mainstream legitimacy when groups use a framing strategy that avoids the rhetoric of old racism, selectively incorporates the discourse of white victimhood, and emphasizes the language of new racism.